Aquaponics: Land Optimization and Business Opportunities in Sedayu Village, Tulung, Klaten: Akuaponik: Optimalisasi Lahan Dan Peluang Usaha Di Desa Sedayu, Tulung, Klaten - Sunarsih Sunarsih; Yahyana Maulina Ilmi; Zarrah Ilhami (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Sedayu Village, Tulung District, Klaten Regency is a rural area, where there is still a lot of vacant land that is not used. In fact, almost every resident in Sedayu has a large and productive yard or vacant land to use. In order to optimize the vacant land, it is necessary to carry out an aquaponics program, namely for the cultivation of catfish and kale. This program is expected to strengthen food and open up business opportunities for the community, so that the level of welfare in Sedayu can increase. This research contains how to optimize land and create new business opportunities by cultivating catfish and water spinach plants using the aquaponics method